CONTROL ALGORITHM FOR IMPLEMENTING A MATHEMATICAL MODEL FOR ASSESSING THE EFFECTIVENESS OF SCENARIO MANAGEMENT AS A TOOL FOR ENSURING THE SECURITY OF A STRATEGIC FACILITY - Azarenko, O.; Honcharenko, Yu.; Diviziniuk, M.; Shevchenko, R.; Shevchenko, O. (Municipal economy of cities. Series: «Economy science», 2024)
Ensuring the safety of critical infrastructure facilities and other strategic objects is one of the main tasks of Ukraine as a state defending itself against military aggression. To accomplish this task, the authors developed a mathematical model of scenario management as a tool to ensure a strategic object’s security. However, the problem arises that, due to the nonlinearity of the processes under consideration, the theoretical solutions rely on assessing various controlling influences and, if necessary, their corrections to obtain the planned result. This article aims to develop a control algorithm for implementing a mathematical model to assess the effectiveness of scenario management as a tool for ensuring the security of a strategic object. For this, it is necessary to complete the following tasks: to consider a mathematical model for assessing the effectiveness of scenario management as a tool for ensuring the safety of a strategic object; develop the structure of the control algorithm for the implementation of this mathematical model; analyse the structure of the algorithm and make recommendations about the need to create the basic procedures for its implementation. A proposed control algorithm for implementing a mathematical model for assessing the effectiveness of scenario management as a tool for ensuring the security of a strategic object is a hierarchical structure of nine blocks (or modules) located at seven hierarchical levels, connected by direct and feedback links. It assesses the effectiveness of solving private tasks to ensure the security of a strategic object under protection, adjusting control influences aimed at implementing the selected scenario management option. At the first hierarchical level is the module for determining the parameters of systematisation of critical infrastructure conglomeration security data. The second level includes the object conglomeration module, which consists of submodules. The third hierarchical level contains the module for collecting data by parameters. The fourth level has two modules. The first is for performing calculations, and the second is for selecting evaluation parameters. It also aims to supplement or reject duplicate data. The fifth hierarchical level also contains two modules. The first is evaluating results according to particular criteria, and the second is the selection of evaluation criteria. The sixth level is the results interpretation module. This module provides the final assessment of the facility’s safety. The seventh hierarchical level is the module for making decisions on adjusting control actions. For the correct, practical application of this control algorithm to assess the effectiveness of solving private tasks to ensure the security of strategic and critical infrastructure objects under protection, it is necessary to develop the procedures for its application in detail.